2017
DOI: 10.17706/ijeeee.2017.7.1.70-78
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyber Threats on Customer’s Behaviour in e-Banking Services

Abstract: Cybercrime and information security are always parallel to each other's. Computer fraudsters are always trying to gain unauthorized access to the information of financial and business sectors for fraudulent activities. The customers of online banking always fear for their financial data when dealing with online banking and its services. It is certainly affecting the use of online banking services and its customer's behavior. There is a need to create awareness among online banking customer on how to avoid the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 0 publications
0
27
0
4
Order By: Relevance
“…However, the study did not specify which aspect of efficiency in the Pakistan banking sector was really affected by cybercrime. Examining the impacts of cyber threats on the attitude of customers using e-banking services, Ali et al (2017) indicated that only 31% of the respondents confirmed to be aware of the cyber threat categories mentioned in their survey. By implications, it means an approximate 70% of the online users were not aware of the mentioned threats.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the study did not specify which aspect of efficiency in the Pakistan banking sector was really affected by cybercrime. Examining the impacts of cyber threats on the attitude of customers using e-banking services, Ali et al (2017) indicated that only 31% of the respondents confirmed to be aware of the cyber threat categories mentioned in their survey. By implications, it means an approximate 70% of the online users were not aware of the mentioned threats.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kết quả nghiên cứu cho thấy rủi do trong vấn đề an ninh mạng tại các ngân hàng thương mại tại Việt Nam về cơ bản giống như cách thức mà các tin tặc thường xuyên sử dụng khi tấn công mạng (Ali et al, 2017;CRIC, 2005;DOPUK, 2013;Kaur, 2015;Pandalabs, 2012;RSA, 2016;Web, 2013). Việc các ngân hàng thương mại đã tập trung đầu tư nhất để đảm bảo đạt được đến mức độ an minh mạng trong hoạt động giao dịch ngân hàng thương mại.…”
Section: Thảo Luận Kết Quảunclassified
“…Ngày càng có nhiều phần mềm độc hại ẩn danh khác nhau có thể được sử dụng cho mục đích tấn công mạng máy tính bởi những kẻ tội phạm mạng. (Ali et al, 2017) 6 Tự động hóa gian lận ngân hàng trực tuyến (Automating Online Banking Fraud): Tội phạm mạng và những kẻ gian lận máy tính hiện đã thực hiện những bước tiến xa hơn với sự trợ giúp của Hệ thống chuyển giao tự động (Transfer Systems). Một hệ thống mới đã được bắt đầu cho tự động hóa hệ thống gian lận ngân hàng trực tuyến bằng cách kết nối với các biến thể phần mềm độc hại SpyEye và ZeuS như một phần của tệp WebInject, là tệp văn bản có nhiều mã JavaScript và HTML.…”
unclassified
See 2 more Smart Citations